OHSAS 18001: sustainable construction / Mohd Arif Marhani, Hamimah Adnan and Faridah Ismail. - Marhani, Mohd Arif; Adnan, Hamimah; Ismail, Faridah (Universiti Teknologi MARA Cawangan Selangor, 2018)
OHSAS 18001 was proposed to promote an organisation manages occupational health and safety (OH&S) risks and further improved work operations. However, the positive efforts by the government of Malaysia to improve the implementation, use and acceptance level of OHSAS 18001 are still not remarkable. Hence, the objectives of this paper are to determine the level of acceptance and to establish the best alternative practice in implementing OHSAS 18001. Questionnaire surveys were used as the research method. It is hoped that the implementation of OHSAS 18001 can stimulate the atmosphere of safety culture towards sustainable construction in the Malaysian construction industry.